Pengaruh Pemberian Berbagai Dosis Rhizobium terhadap Produktivitas Tanaman Kedelai Edamame (Glycine max (L.) Merill.): Effectiveness of Chicken Manure and Various Doses of Rhizobium on the Productivity of Edamame Soybean Plants (Glycine max (L.) Merill.) - Munir, Muhammad Rifki; Lias, Syamsul Arifin (Universitas Hasanuddin, 2025)
Background. Edamame soybeans are a type of soybean with larger pods than common soybeans and contain a relatively high nutritional value. Nitrogen availability is a key factor in determining the productivity of edamame soybean (Glycine max (L.) Merill.), and the application of Rhizobium is one of the effective methods to enhance biological nitrogen fixation. Objective. This study aimed to evaluate the effect of various Rhizobium doses on the productivity of edamame soybean plants. Method. The experiment was conducted at the experimental field of the Soil Research Institute from August to October 2025 using a one-factor randomized block design (RBD) with four Rhizobium dose levels: no inoculation, 7.5 g/kg seed, 15 g/kg seed, and 22.5 g/kg seed, each replicated three times. Local edamame soybean seeds were incubated with Rhizobium according to the treatment dose prior to planting. Observations included root nodule distribution, nodule size, nodule color, number of leaves, plant height, flowering time, and fresh pod weight per plot. Results. Initial soil analysis indicated acidic conditions (pH 5.0–5.5) with low nutrient content. After treatment, all soil chemical parameters improved, with soil pH increasing to 6.15–6.67, organic C to 1.61–1.90%, total N up to 0.29%, available P₂O₅ up to 16.48 ppm, cation exchange capacity (CEC) up to 23.96 cmol(+)/kg, and increases in Ca, Mg, Na, and K cations. The 22.5 g/kg seed Rhizobium treatment (I3) tended to produce the highest plant growth (33.2 cm height and 27.8 leaves) and the highest soil pH, organic C, and P₂O₅ values, although the differences were not statistically significant for all growth and yield parameters. Conclusion. Analysis of variance showed that the Effect of Various Rhizobium Doses had no significant effect on all treatments. Root nodule distribution and color parameters indicated that nitrogen fixation was not occurring effectively.